Dame Cicely Saunders - Shotter, E. F. (Journal of medical ethics, 2006)
Cicely Saunders, the founder of St Christopher’s Hospice, who pioneered palliative care as a new specialty, died in July 2005 at the age of 87. She was an active supporter of the London Medical Group (a student group for the study of issues raised by the practice of medicine that concern other disciplines), lecturing annually under its auspices from 1963 until, in her own words, she “drew stumps” in 1989. Although she invariably lectured under the title of “The Nature and Management of Terminal Pain”, no lecture was repeated and it became clear, in retrospect, that she had been reporting …